HAM, AHMADIYAH DAN HETERODOKSI BERAGAMA - Bambang Saiful Ma'arif (Millah: Journal of Religious Studies, 2012)
This working paper elaborates guarantee of Universal Declaration of Human Rights (DUHAM) and the Basic Constitution (UUD) 1945 on freedom of religion and its implementation in Indonesia, as well as how the Ahmadiyah, which is regarded as a religions heterodoxy, gets the freedom. Individual freedom to live make them do accordance with their will is guaranteed by Universal Declaration of Human Rights (DUHAM), including freedom of religion and belief. But in practice, especially in Indonesia, Ahmadiyah get many obstacles to practice their faith, particularly when doctrine (understanding) believed by a person or group does not accord with the given or old understanding. As a result, the freedom of religion is tied. In fact, human freedom is guaranteed by Universal Declaration of Human Rights (DUHAM).